Kajian Optimalisasi Sistem Irigasi Rawa (Studi Kasus Daerah Rawa Semangga Kabupaten Merauke Propinsi Papua) - Pakpahan, Darwin; Suripin, Suripin; Sangkawati Sachro, Sri (MEDIA KOMUNIKASI TEKNIK SIPIL, 2014)
Population growth is increasing, but it is not accompanied by an increase in food needs impartial. Indonesian swamp land potential of about 33.4 million ha, consisting of tidal swamp 20.1 million ha and 13.3 million ha of lowland swamp. The Government has made the development of swamps into agricultural land, including the Semangga swamp area (4,000 ha) The cropping pattern of rice (100%) - crops (40%) – “bero”. The problem faced are; the length is 7-month of dry season and low agricultural production, are therefore likely to swamp irrigation system optimalization. The method used to carry out water balance analysis and performance assessment of irrigation system include; the physical condition of irrigation, the application of the system of planting and water delivery techniques to the use of land for a year, then performed according to the potential land development plan and water resources available. Results of water balance analysis on Semangga Swamp Area existing condition indicate that water deficit occurred during the second growing season crops (May-July) and in December. So do the appropriate development plan defined cropping pattern III, namely rice (100%) - crops (60%) - crops (45%) with the addition of a total area of 1,000 ha through the use Kumbe River and Maro River and other water reservoirs to overcome deficits in the availability of water in the dry season that is equal to 2.5m³/s (April to August and October to December), while 6.5m³/s in September, 72.40% irrigation system performance with good category.